Family planning: attitudes and practices among postnatal women and their husbands in Obstetric and Gynecology Clinic, Hospital Universiti Sains Malaysia (HUSM) - Baser, Nor Idzziana (Universiti Sains Malaysia, 2009)
Lack of awareness towards family planning among men and women is an issue needed to take into account. This quantitative study was conducted to identify the relationship between attitudes and practice of family planning among men and women in Obstetric and Gynecology Clinic, HUSM. This research is a cross-sectional, descriptive study using questionnaire. The sample is 65 men and women selected from Obstetric and Gynecology Clinic, HUSM. Self-administer questionnaire was utilized and the questionnaire consists of three sections. Section A consists of respondent's demographic characteristics, Section B consists of 26 attitudinal statements and Section C consists of one question regarding contraceptives practice. Data was analyzed by Chi-square test from Statistical Package for Social Science (SPSS) version 12 software. More than half of the men and women had positive attitudes towards family planning, but yet only minority of them uses contraceptives method. These quantitative findings contrast with results from other research in other countries. Educated men and women's tend to practice family planning due to their knowledge to the use of contraceptives. Men and women who wanted more children were reluctant to practice family planning. Understanding family planning thoroughly is the key concept in practicing it. Throughout this study, sociocultural and traditional norms give a huge impact on practice of family planning. Therefore, intervention efforts should address these issues and mold action plans appropriate to the situation.